Welfare reform and beyond : the future of the safety net - Sawhill, Isabel V.; Brookings Institution (Washington, D.C. : Brookings Institution, 2002)
The Brookings Institution's Welfare Reform & Beyond Initiative was created to inform the critical policy debates surrounding the upcoming congressional reauthorization of the Temporary Assistance for Needy Families (TANF) program and a number of related programs that were created or dramatically altered by the 1996 landmark welfare reform legislation. The goal of the project has been to take the large volume of existing and forthcoming research studies and shape them into a more coherent and policy-oriented whole. This capstone collection gathers twenty brief essays (published between January 2001 and February 2002) that focus on assessing the record of welfare reform, specific issues likely to be debated before the TANF reauthorization, and a broader set of policy options for low-income families. It is a reader-friendly volume that will provide policymakers, the press, and the interested public with a comprehensive guide to the numerous issues that must be addressed as Congress considers the future of the nation's antipoverty policies. The collection covers the following topics and features a new introduction from the editors: - An Overview of Effects to Date - Welfare Reform Reauthorization: An Overview of Problems and Issues - A Tax Proposal for Working Families with Children - Welfare Reform and Poverty - Reducing Non-Marital Births - Which Welfare Reforms are Best for Children' - Welfare and the Economy - What Can Be Done to Reduce Teen Pregnancy and Out-of-Wedlock Births' - Changing Welfare Offices - State Programs - Welfare Reform and Employment - Fragile Families, Welfare Reform, and Marriage - Health Insurance, Welfare, and Work - Helping the Hard-to-Employ - Sanctions and Welfare Reform - Child Care and Welfare Reform - Job Retention and Advancement in Welfare Reform - Housing and Welfare Reform - Non-Citizens - Block Grant Structure - Food Stamps - Work Support System - Possible Welfare Reform in the Cities.
pt. I. Introduction and summary. An overview / Isabel Sawhill, R. Kent Weaver, and Andrea Kane -- Results to date / Isabel Sawhill [and others] -- Problems and issues for reauthorization / Isabel Sawhill [and others] -- pt. II. State responses. State policy choices under welfare reform / Thomas Gais and R. Kent Weaver -- Changing welfare offices / Irene Lurie -- Sanctions and welfare reform / Dan Bloom and Don Winstead -- pt. III. Results to date. Welfare reform and poverty / Ron Haskins and Wendell Primus -- Which welfare reforms are best for children? / Pamela A. Morris and Greg J. Duncan -- From welfare to work : what the evidence shows / Robert A. Moffitt -- pt. IV. TANF funding and the economy. The structure of the TANF block grant / R. Kent Weaver -- Welfare and the economy / Rebecca M. Blank -- pt. V. Encouraging and rewarding work. Welfare reform and the work support system / Isabel Sawhill and Ron Haskins -- The role of education and training in welfare reform / Judith M. Gueron and Gayle Hamilton -- Job retention and advancement in welfare reform / Nancye Campbell, John K. Maniha, and Howard Rolston -- Helping the hard-to-employ / LaDonna Pavetti -- pt. VI. Family formation. Reducing non-marital births / Paul Offner -- Fragile families, welfare reform, and marriage / Sara McLanahan, Irwin Garfinkel, and Ronald B. Mincy -- What can be done to reduce teen pregnancy and out-of-wedlock births? / Isabel Sawhill -- pt. VII. Related programs. Food stamps and welfare reform / Michael Wiseman -- Health insurance, welfare, and work / Alan Weil and John Holahan -- Child care and welfare reform / Gina Adams and Monica Rohacek -- Welfare reform and housing / Rebecca Swartz and Brian Miller -- Welfare benefits for non-citizens / Michael Fix and Ron Haskins.
Includes bibliographical references.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
English.
Keywords: Temporary Assistance for Needy Families (Program); Temporary Assistance for Needy Families (Programme); Temporary Assistance for Needy Families (Program); Temporary Assistance for Needy Families (Program); Public welfare -- United States; Welfare recipients -- Employment -- United States; Aid to families with dependent children programs -- Law and legislation -- United States; Public welfare administration -- Law and legislation -- United States; Aide sociale -- États-Unis.; Aide sociale -- Bénéficiaires -- Travail -- États-Unis.; Aide sociale aux familles avec enfants à charge -- Droit -- États-Unis.; Aide sociale -- Administration -- Droit -- États-Unis.; POLITICAL SCIENCE -- Public Policy -- Social Services & Welfare; SOCIAL SCIENCE -- Human Services; Welfare recipients -- Employment -- United States; Public welfare -- United States; Aid to families with dependent children programs -- Law and legislation -- United States; Public welfare administration -- Law and legislation -- United States; Aid to families with dependent children programs -- Law and legislation; Public welfare; Public welfare administration -- Law and legislation; Welfare recipients -- Employment; United States; Sozialhilfe; Reform; Aufsatzsammlung; Prognose; USA